Gene Therapy for Liver Cancers: Current Status from Basic to Clinics - Kamimura, Kenya (Cancers (Basel), 2019)
The liver is a key organ for metabolism, protein synthesis, detoxification, and endocrine function, and among liver diseases, including hepatitis, cirrhosis, malignant tumors, and congenital disease, liver cancer is one of the leading causes of cancer-related deaths worldwide. Conventional therapeutic options such as embolization and chemotherapy are not effective against advanced-stage liver cancer; therefore, continuous efforts focus on the development of novel therapeutic options, including molecular targeted agents and gene therapy. In this review, we will summarize the progress toward the development of gene therapies for liver cancer, with an emphasis on recent clinical trials and preclinical studies.